Investigation into the sero-molecular prevalence of Brucella melitensis in small ruminants in districts Mohmand and Charsadda Khyber Pakhtunkhwa Pakistan - Sohaib Ul Hassan; Farhan Anwar Khan; Muhammad Shuaib; Muhammad Shahid; Said Sajjad Ali Shah; Shahrood Ahmed Siddiqui; Anthony Pokoo-Aikins; Ayman A. Swelum (PLoS ONE, 2025)
Globally, ruminants contribute largely to the livelihood and supply of quality food for human consumption. However, small ruminants face numerous problems, including infectious diseases, in lower- and middle-income countries (LMIC). Brucellosis is one of the important zoonotic diseases affecting the range of animals caused by Brucella species, including Brucella abortus and Brucella mellitensis. Although brucellosis caused by B. mellitensis in small ruminants has never been reported in the study areas, its zoonotic importance can never be underestimated. Therefore, this study was designed to investigate the sero-molecular prevalence of B. mellitensis in small ruminants in districts Mohmand and Charsadda of Khyber Pakhtunkhwa, Pakistan. A total of 400 blood samples were collected from sheep and goats (n = 200 from each species) and analyzed by Rose Bengal precipitation test (RBPT), the indirect enzyme-linked immunosorbent assay (i-ELISA) and polymerase chain reaction (PCR). The findings of the study indicated 13.5% and 7% of sheep while 12.5% and 12.5% of goat’s samples by RBPT and (i-ELISA) respectively. The species-specific PCR confirmed B. abortus in 70% of sheep samples and 37.5% of goat’s samples and B. mellitensis in 25% of sheep and 62.5% of goat’s samples by targeting IS711. The findings of the study concluded that B. abortus and B. melitensis were circulating in sheep and goats with a higher prevalence in the study areas. This study detected the presence of B. mellitensis for the first time in small ruminants in the study areas.